P-wave anisotropy, mantle wedge flow and olivine fabrics beneath Japan - Liu, Xin; Zhao, Dapeng (Geophysical journal international, 2017)
Summary We present a new 3-D anisotropic P-wave velocity (Vp) model for the crust and upper mantle of the Japan subduction zone obtained by inverting a large number of high-quality P-wave traveltime data of local earthquakes and teleseismic events. By assuming orthorhombic anisotropy with a vertical symmetry axis existing in the modeling space, isotropic Vp tomography and 3-D Vp azimuthal and radial anisotropies are determined simultaneously. According to a simple flow field and the obtained Vp anisotropic tomography, we estimate the distribution of olivine fabrics in the mantle wedge. Our results show that the forearc mantle wedge above the subducting Pacific slab beneath NE Japan exhibits an azimuthal anisotropy with trench-parallel fast velocity directions (FVDs) and Vhf > Vv > Vhs (here Vv is Vp in the vertical direction, Vhf and Vhs are P-wave velocities in the fast and slow directions in the horizontal plane), where B-type olivine fabric with vertical trench-parallel flow may dominate. Such an anisotropic feature is not obvious in the forearc mantle wedge above the Philippine Sea (PHS) slab under SW Japan, probably due to higher temperatures and more fluids there associated with the young and warm PHS slab subduction. Trench-normal FVDs and Vhf > Vv > Vhs are generally revealed in the mantle wedge beneath the arc and backarc in Japan, where E-type olivine fabric with FVD-parallel horizontal flow may dominate. Beneath western Honshu, however, the mantle wedge exhibits an anisotropy of Vv > Vhf > Vhs and so C-type olivine fabric may dominate, suggesting that the water content is the highest there, because both the PHS and Pacific slabs exist there and their dehydration reactions release abundant fluids to the overlying mantle wedge.